Etika Ritual Hindu di Bali Menghadapi Masa Pandemi - Yunitha Asry Diantary (Satya Widya: Jurnal Studi Agama, 2021)
Theologically, Hindus have three basic frameworks that serve as guidelines in carrying out their religious life. Tattwa which is the philosophical substance of every activity and symbol; morality which is a supporting virtue which plays an important role in the order of everyday human life; as well as acara which include ritual activities, which implement tattwa and moral values in the form of a more real religious system in the cultural dimension. Ritual activities or sacred actions carried out by Hindus are an expression of the meaning of the yajna or holy sacrifices that are sincere. The Hindu religious ritual can be performed every day or on certain holy days, which is a form of gratitude and devotion to the Lord Almighty by Hindus. Without an event, religion is just a set of teachings that will not appear in the phenomenal world. Since the Covid-19 pandemic until now, the government has issued a “new normal” policy. This concerns many aspects of community life, including in the religious field. All religious activities, especially those carried out by the Balinese Hindu community, are limited. Changes in social behavior in the implementation of religious rituals have experienced a revolution that can be seen that if we observe more closely, today's society prioritizes security ethics but does not reduce the meaning of rituals, so that the implementation of religious activities is not buried in activities in the pandemic period.